Healthy Living: Diabetes - Linda B. Bobroff; Karla P Shelnutt; Paulina Wittkowsky (EDIS)
Diabetes is a serious health condition that occurs when a person’s body has difficulty making or using insulin, which results in high blood glucose (blood sugar) and can lead to other complications. This revised 3-page fact sheet covers the effects of high blood glucose, who is at risk, the symptoms and management of the condition, and additional resources for those with or at risk of developing diabetes. Written by Linda B. Bobroff, Karla P. Shelnutt, and Paulina Wittkowsky, and published by the UF Department of Family Youth and Community Sciences, July 2015.